Histopathological differences between vitiligo and lichen sclerosus et atrophicus using quantitative immunohistochemical analysis - Park, Young Joon; Lee, Heera; Park, Hyoung Soo; Kim, You Chan (Frontiers in Medicine, 2023)
Introduction Lichen sclerosus et atrophicus (LS) is rare skin condition characterized by the presence of whitish patches primarily affecting the genital and perianal areas, though it can occur other parts of the body. LS may result in skin depigmentation without textural changes and should be differentiated from vitiligo. However, the histopathological features of hypopigmentation during vitiligo and LS have rarely been compared and have not been precisely described using quantitative immunohistochemical analysis. This study, therefore, aimed to investigate and compare the pigmentary characteristics of LS and vitiligo lesions using histochemical and immunohistochemical staining. Methods We included 31 and 46 patients diagnosed with LS and vitiligo, respectively, at Ajou University Hospital between March 2009 and March 2020 in this study. Their medical charts and skin biopsy specimens were retrospectively reviewed. Additionally, Fontana–Masson staining for melanin and immunohistochemical staining for Melan-A, NKI/beteb, tyrosinase, and microphthalmia-associated transcription factor was performed. Results The melanin content, as well as the number of melanocytes was, in general, significantly higher in the epidermis of patients in the LS group compared with that in the vitiligo group. However, 22.6% of LS tissues showed less melanin pigmentation, 25.8% of LS specimens exhibited a lower number of melanocytes, and 29.0% of LS specimens demonstrated less melanocyte activity when compared with the average of vitiligo specimens. Conclusion As lower melanin pigmentation and the near absence number of melanocytes were also observed in several LS specimens, both the clinical and histological findings must be comprehensively reviewed to differentiate vitiligo from LS.